Comparison of Simple Additive Weighting (SAW) and Promethee Methods in Rice Quality Selection - Fatma Sari Hutagalung; Budi Kurniawan Hutasuhut; Al-Khowarizmi Al-Khowarizmi (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2020)
Rice is one of the foods that contain enough nutrients and boosters for the human body, because it contains ingredients that are easily converted into energy. In Indonesia there are more than 1000 types of rice varieties, and every year new varieties appear. Farmers find it difficult to determine which type of rice they will plant. Farmers must try each type of different varieties each season, to find out which quality rice. For this reason, a decision support system is needed to select qualified rice. In the decision support system two methods of comparison are used, namely the Simple Additive Weighting (SAW) method and PROMETHEE. The Simple Additive Weighting (SAW) method will be compared to the PROMETHEE method. In a decision support system, the data used will be changed first into the form of weights that have been determined based on parameters. The types of rice used are paddy and hybrid rice. Both methods will be compared based on the length of time of execution and the success rate of selecting rice quality. The end result of the system for rice using both methods is the angke for lowland rice and the 6 ceva hipa for hybrid rice. with an execution time of 570,0008 milliseconds for the SAW method, and PROMETHEE method with an execution time of 12488.2 milliseconds in lowland rice, and 1140,006 milliseconds for the duration of SAW execution, 16400,029 for the duration of PROMETHEE for hybrid rice. The SAW method is faster than the promethee method.